Metagenomic characterization of the microbiomes in five different body habitats of otherwise healthy individuals with periodontal disease - Oh, Sujin; Lee, Hyo-Jung; Park, Kyoung Un (Frontiers in Cellular and Infection Microbiology, 2023)
Recent studies have proposed several plausible mechanisms supporting the association between periodontal disease and systemic disease. However, characterizing the microbial communities in individuals with periodontal disease before onset of other diseases is an important first step in determining how the altered microbial state contributes to disease progression. This study established microbiome profiles for five body habitats of carefully selected, otherwise healthy individuals with periodontal disease. Blood, oral (buccal mucosa, dental plaque, and saliva), and stool samples were collected from ten healthy subjects with periodontal disease. Using 16S rRNA metagenomics, the taxonomic and functional compositions of microbiomes were investigated. The most predominant phylum in blood and stool was Bacillota. Pseudomonadota accounted for the largest proportion of microbes in the buccal mucosa and saliva, whereas Bacteroidota were the most prevalent in dental plaque. Differential abundance analysis revealed that 12 phyla and 139 genera were differentially abundant between body habitats. Comparison of alpha diversity showed that the blood microbiome has the most diverse community close to neither oral nor stool microbiomes. We also predicted the functional configurations of the microbiome in otherwise healthy subjects with periodontal disease. Principal coordinate analysis based on functional abundance revealed distinct clustering of the microbial communities between different body habitats, as also observed for taxonomic abundance. In addition, 13 functional pathways, including lipopolysaccharide biosynthesis, glutathione metabolism, and proteasome, showed differential expression between habitats. Our results offer insight into the effects of the microbiome on systemic health and disease in people with periodontal disease.